Management of PKL Supervisor Teachers in Fostering Work Discipline of Students at SMKN 2 Bone - Sri Luktafiani; Baharuddin Baharuddin; Muh. Qaddafy; Andi Halimah; Sitti Aisyah Chalik (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Internships (PKL) often face the problem of low work discipline among students due to a lack of understanding of the rules, minimal supervision, and differences in work culture between schools and industry. This study analyzes the management of supervising teachers in fostering work discipline among students during PKL at SMKN 2 Bone. The study was conducted from January 14 to February 14, 2025, using qualitative descriptive methods through observation, interviews, and documentation. Discipline development begins with planning, such as selecting the PKL location, providing supplies, and establishing rules between the school and industry. During implementation, supervisors provide direction and motivation before and during the PKL, as well as imposing sanctions so that students understand the importance of work discipline. Supervision is carried out directly by the supervising teachers and industry, and indirectly through periodic student reports. This study recommends improving work discipline development through intensive communication, school-industry coordination, systematic evaluation, and parental supervision. With good management and the involvement of all parties, student work discipline during PKL can be improved to prepare them for the world of work.